Comparison of manual and automatic cell count methods for synovial fluid: A prospective study - Alıç, Taner; Şahin, Mustafa; Savcı, Ünsal; Çalbıyık, Murat; Kayadibi, Hüseyin (Journal of Surgery and Medicine, 2022)
Background/Aim: Cell count measurement methods in the synovial fluid are still a current problem in orthopedic practice. Knowing the cell count in the synovial fluid is important for the assessment of a variety of orthopedic and rheumatologic diseases. We aimed to assess the correlation of WBC and RBC results obtained with a complete blood count analyzer with that obtained by a manual cell count. Methods: The WBC and RBC count in the synovial fluid of 43 patients undergoing gonarthrosis surgery were determined by a Mindray BC-6800 hematology analyzer. The study groups were defined as manual cell count (MC), hemogram mode (HM), and body fluid mode (BFM). All samples were analyzed twice consecutively, and the mean results were calculated. Cell counting was performed using different methods in the same samples and compared statistically. Results: The mean age of the patients was 60.9 years, and there were 17 males (39.5%) and 26 females (60.5%). The WBC and RBC counts in the synovial fluid samples were determined using manual cell count, and the HM and BFM on a Mindray BC-6800 automatic hematology analyzer. WBC counts significantly differed between MC and BFM, and RBC counts significantly differed between HM-MC and HM-BFM (P=0.001, P=0.001, P=0.001, respectively). There was a significant positive correlation between BFM and MC in WBC counts (r=0.633, P<0.001), with no statistically significant correlations identified between other methods. For RBC counts, there was a significant positive correlation between BFM and MC results (r=0.363, P=0.032). Conclusion: While the body fluid mode in hematology analyzers can be recommended for obtaining an RBC count in the synovial fluid, the hemogram mode may be recommended for the WBC count.